OUTCOME OF PREVIOUS RESEARCH REGARDING NORMATIVE AND POSITIVE ACCOUNTING THEORIES: FINDINGS AND IMPLICATIONS - VIORICA MIRELA STEFAN-DUICU; MIHAELA SUDACEVSCHI (Global Economic Observer)
This paper contains a brief vision over the way of exposure and integration of the accounting theory as a whole within a continuous evolutionary environment. Since the issuance of the fundamental forming framework of accounting theories, the organizational environment has continuously focused on shaping these theories to ensure the optimal undergoing of activities. This aspect has a pronounced interest in present days and generates an important process in the development of the organizational framework both conceptually, theoretically, and practically, through targeted measures. Accounting theory consists of logical reasoning that aids in the evaluation, improvement and implementation of financial procedures and practices in companies, aiming to achieve optimal alignment within the economic-financial business environment. The purpose of this article is to compactly summarize the comprehensive critiques and analyses of different perspectives of accounting theory provided by important papers and studies, which represent valuable resources for researchers in the field and beyond.